Risk Factors for Disability Pension among Young Adults Diagnosed with Attention-deficit Hyperactivity Disorder (ADHD) in Adulthood. Issue 5 (March 2022) - Chen, Lingjing; Mittendorfer-Rutz, Ellenor; Björkenstam, Emma; Rahman, Syed; Gustafsson, Klas; Taipale, Heidi; Tanskanen, Antti; Ekselius, Lisa; Helgesson, Magnus
Objective: To investigate risk factors of disability pension (DP) in young adults diagnosed with ADHD in Sweden. Method: In total, 9718 individuals diagnosed with incident ADHD in young adult age (19–29 years) 2006 to 2011, were identified through national registers. They were followed for 5 years and Cox regression models were applied to analyze the DP risk (overall and by sex), associated with socio-demographics, work-related factors, and comorbid disorders. Results: Twenty-one percent of all received DP. Being younger at diagnosis (hazard ratio [HR] = 1.54; 95%confidence interval [CI] 1.39–1.71); low educational level (HR = 1.97; 95%CI 1.60–2.43 for <10 years); work-related factors at baseline (no income from work [HR = 2.64; 95%CI 2.35–2.98] and sickness absence >90 days [HR = 2.48; 95%CI2.17–2.83]); and schizophrenia/psychoses (HR = 2.16; 95%CI 1.66–2.80), autism (HR = 1.87; 95%CI 1.42–2.46), anxiety (HR = 1.34; 95%CI 1.22–1.49) were significantly associated with an increased risk of DP. Similar risk patterns were found in men and women. Conclusion: Work-related factors and comorbid mental disorders need to be highlighted in early vocational rehabilitation for individuals with ADHD.